1996
DOI: 10.1074/jbc.271.43.26453
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Turnover of Phosphatidylinositol 4,5-Bisphosphate in Caveolin-enriched Membrane Domains

Abstract: Caveolae are small, plasma membrane invaginations that have been implicated in cell signaling. In A431 cells, approximately half of the total cellular phosphatidylinositol 4,5-bisphosphate (PtdIns 4,5-P 2 ) was found to be localized in low density, Triton-insoluble membrane domains enriched in caveolin. Treatment of cells with either epidermal growth factor or bradykinin for 5 min at 37°C resulted in approximately a 50% decrease in this caveolar PtdIns 4,5-P 2 with no change in the levels of plasma membrane Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
239
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(265 citation statements)
references
References 26 publications
24
239
1
1
Order By: Relevance
“…However, PIP 2 is likely to be more concentrated in the inner leaflet of plasma membranes. In addition, there is a possibility for the occurrence of PIP 2 -enriched membrane microdomains, as those domains have been reported in mammalian cells (30). Furthermore, this new PLD is also stimulated by PIP.…”
Section: Discussionmentioning
confidence: 83%
“…However, PIP 2 is likely to be more concentrated in the inner leaflet of plasma membranes. In addition, there is a possibility for the occurrence of PIP 2 -enriched membrane microdomains, as those domains have been reported in mammalian cells (30). Furthermore, this new PLD is also stimulated by PIP.…”
Section: Discussionmentioning
confidence: 83%
“…Notably, the identified interaction in this report is reminiscent of the interaction between the caveolar Trp channels and the ER-localized IP3 receptors (Kiselyov et al, 1999;Lockwich et al, 2001). In addition, several studies have shown that caveolae not only contain PLC-␥1, but also 50% of the plasma membrane PIP2, a substrate of PLC-␥1 (Pike and Casey, 1996;Jang et al, 2001).…”
Section: Na/k-atpase As a Scaffoldmentioning
confidence: 99%
“…Moreover, the larger proportion of PIP 2 in cells is localized in caveolin-enriched micro-domains (caveoli) (Pike and Casey, 1996). Caveoli are known to be signal initiation sites where many intracellular signaling molecules, such as EGF receptor, G-α subunit, ras, etc.…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%
“…However, until now, a protein tyrosine phosphatase acting on tyrosyl phosphorylated PLC-γ1 has not been identified. Discovery of an in vivo protein tyrosine phosphatase for PLC-γ1 would widely extend our knowledge of the regulatory mechanism of PLC-γ1.Recently we have identified that PTP-1B, a cytosolic protein tyrosine phosphatase, can dephosphorylate PLC-γ1 in vitro and vvivo (Kim et al, unpublished data).Moreover, the larger proportion of PIP 2 in cells is localized in caveolin-enriched micro-domains (caveoli) (Pike and Casey, 1996). Caveoli are known to be signal initiation sites where many intracellular signaling molecules, such as EGF receptor, G-α subunit, ras, etc.…”
mentioning
confidence: 99%